Presence of Electrostatically Adsorbed Polysaccharides Improves Spray Drying of Liposomes. Issue 2 (16th January 2013) - Karadag, Ayse; Özçelik, Beraat; Sramek, Martin; Gibis, Monika; Kohlus, Reinhard; Weiss, Jochen
Abstract Spray drying of liposomes with conventional wall materials such as maltodextrins often yields nonfunctional powders, that is, liposomes break down during drying and rehydration. Electrostatically coating the surface of liposomes with a charged polymer prior to spray drying may help solve this problem. Anionic lecithin liposomes (approximately 400 nm) were coated with lower (approximately 500 kDa, LMW‐C) or higher (approximately 900 kDa, HMW‐C) molecular weight cationic chitosan using the layer‐by‐layer depositing method. Low (DE20, LMW‐MD) or high molecular weight (DE2, HMW‐MD) maltodextrin was added as wall material to facilitate spray drying. If surfaces of liposomes (1%) were completely covered with chitosan (0.4%), no bridging or depletion flocculation would occur, and mean particle diameters would be approximately 500 nm. If maltodextrins (20%) were added to uncoated liposomes, extensive liposomal breakdown would occur making the system unsuitable for spray drying. No such aggregation or breakdown was observed when maltodextrin was added to chitosan‐coated liposomes. Size changed little or even decreased slightly depending on the molecular weight of maltodextrin added. Scanning electron microscopy images of powders containing chitosan‐coated liposomes revealed that their morphologies depended on the type of maltodextrin added. Powders prepared with LMW‐MD contained mostly spherical particles while HMW‐MD powders contained particles with concavities and dents. Upon redispersion, coated liposomes yielded back dispersions with particle size distributions similar to the original ones, except for LMW‐C coated samples that had been spray dried with HMW‐MD which yielded aggregates (approximately 30 μm). Results show that coating of liposomes with an absorbing polymer allows them to be spray dried with conventional maltodextrin wall materials. Practical Application: Liposomes have attracted considerable attention in the food and agricultural, biomedical industries for the delivery of functional components. However, maintaining their stability in aqueous dispersion represents a challenge for their commercialization. Spray drying may promise a solution to that problem. However, prior to this study spray drying of liposomes often led to the loss of structural integrity. Results of this study suggest that spray drying might be used to produce commercially feasible liposomal powders if proper combinations of adsorbing and nonadsorbing polymers are used in the liquid precursor system.